The children's book of the movies : explore the magical, behind-the-scenes world of the movies - Baggaley, Ann; DK Publishing, Inc. (2014)
Provides information about movies, chronicling their history from the early moving pictures to today; detailing how stunts and screen writing are done; and profiling famous actors, producers, and directors.
A journey through film: the story of the movies -- Moving pictures -- From silence to sound -- Charlie Chaplin -- Stranger than fiction -- Going to the movies -- Heroes and villains -- Walt Disney -- Glorious Technicolor -- The Wizard of Oz -- The Golden Age of the movies -- Stars of the Golden Age -- Moving to the modern age -- Behind the scenes: from green light to opening night -- Who's who -- Great producers -- Writing a movie -- Attention to detail -- Harry Potter and the Chamber of Secrets -- Make believe -- The world of effects -- Weta -- Animation -- Getting the shot -- Great directors -- Steven Spielberg -- Bright young screen stars -- The Red Balloon -- Animal actors -- The Cave of the Yellow Dog -- Music on film -- Spreading the word -- The red carpet -- Stories on screen: telling stories -- Animated films -- Spirited Away -- Science fiction -- Star Wars: Episode V The Empire Strikes Back -- Scary movies -- King Kong -- Martial arts -- Crouching Tiger, Hidden Dragon -- Choreography -- Musicals -- Bollywood superstars -- Amitabh Bachchan -- Documentaries -- Actors in action -- Stunts on set -- Fairy tale and fantasy -- Alice in Wonderland -- superheroes -- Western -- Butch Cassidy and the Sundance Kid -- Drama -- Jodie Foster -- Comedy -- Jacques Tati -- Detectives and spies -- James Bond -- Playing with film -- So you want to make a movie!
"This book was created in partnership with FILMCLUB (now part of FILM NATION UK)"--Title page verso.
Includes index.
"The theme or content of some movies listed in Children's book of the movies may not be suitable for all children. Please check the film's rating and consider its suitability before letting your child view it"--Title page verso.
Keywords: Motion pictures -- Juvenile literature; Motion pictures -- Appreciation -- Juvenile literature; Motion pictures -- History -- Juvenile literature; Motion pictures; Motion pictures -- Appreciation; Motion pictures -- History